Indicadores da participação feminina na comunidade docente da Universidade Federal de São Carlos em 2017 - Minotto, Ana Aparecida Pires (Universidade Federal de São Carlos, 2018)
To know the female situation and the gender relations in the scientific world contributes to the elaboration of strategies of shifts in the institutional structure of science. These changes are part of the search for gender equity in the academic setting. It is not just about increasing the participation of women in science and technology by increasing and stimulating access. It is necessary to recognize and unveil the sexist biases that are inherent to institutionality and are present among the lines of scientific culture, in search of the transformations of gender relations in science and technology, with the intent of keeping women in the academy and aiming at breaking the "ceiling glass". Thus, this descriptive and exploratory work aims to construct indicators of the participation of female professors in science and technology in a public institution of higher education and research and is guided by the following question of research: how to configure the distribution of female scholars in the scientific community of UFSCar in areas of knowledge, hierarchy and scientific leadership in the year 2017? We sought to identify indicators of female participation in the teaching community of the Federal University of São Carlos (UFSCar), referring to the year 2017. Documentary sources such as institutional reports, the Lattes Platform and the Directory of Research Groups of the National Council of Scientific and Technological Development (CNPq) were used in the research. The data portrays the participation of women in the teaching staff, the leadership of research groups, in the approval of research productivity grants from CNPq and in the exercise of trust functions. In order to analyze these data, the theoretical framework addresses the literature on gender and science derived mainly from Social Studies of Science.
Keywords: Indicadores; Gênero; Ciência; Universidade Federal de São Carlos; Indicators; Gender; Science; Federal University of São Carlos; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS